2017
DOI: 10.3945/ajcn.117.159855
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of whole eggs promotes greater stimulation of postexercise muscle protein synthesis than consumption of isonitrogenous amounts of egg whites in young men

Abstract: Background: Protein in the diet is commonly ingested from whole foods that contain various macro-and micronutrients. However, the effect of consuming protein within its natural whole-food matrix on postprandial protein metabolism remains understudied in humans. Objective: We aimed to compare the whole-body and muscle protein metabolic responses after the consumption of whole eggs with egg whites during exercise recovery in young men. Design: In crossover trials, 10 resistance-trained men [aged 21 6 1 y; 88 6 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(160 citation statements)
references
References 43 publications
5
151
2
2
Order By: Relevance
“…whole egg (both providing 18 g of dietary protein) consumption during post‐exercise recovery in healthy young men revealed a superior 5 h MPS response after whole egg ingestion, despite similar postprandial amino acid profiles after ingestion of these two protein sources (van Vliet et al . ). These findings confirmed the results of a previous study in which whole milk consumption resulted in a greater net uptake of amino acids by skeletal muscle (presumably for use in protein synthesis) compared to ingestion of skimmed milk matched for protein content (Elliot et al .…”
Section: Introductionmentioning
confidence: 97%
“…whole egg (both providing 18 g of dietary protein) consumption during post‐exercise recovery in healthy young men revealed a superior 5 h MPS response after whole egg ingestion, despite similar postprandial amino acid profiles after ingestion of these two protein sources (van Vliet et al . ). These findings confirmed the results of a previous study in which whole milk consumption resulted in a greater net uptake of amino acids by skeletal muscle (presumably for use in protein synthesis) compared to ingestion of skimmed milk matched for protein content (Elliot et al .…”
Section: Introductionmentioning
confidence: 97%
“…However, subjects were able to continue to exercise for 15 to 70 minutes despite being hypoglycemic and their time to exhaustion was not significantly different from euglycemic subjects. Glucose ingestion at rates of 40 or 80 g•h −1 prevented the hypoglycemia, but did not significantly increase time to fatigue [58].…”
Section: Carbohydrates During Exercise To Maintain Euglycemiamentioning
confidence: 84%
“…However, the impact of hypoglycemia or its prevention does not always consistently improve endurance capacity [57,58]. Felig et al observed hypoglycemia in approximately one third of subjects cycling to exhaustion on 60-65% VO2max in a fasted state [58].…”
Section: Carbohydrates During Exercise To Maintain Euglycemiamentioning
confidence: 99%
See 2 more Smart Citations